Variations in outcome and costs among NHS providers for common surgical procedures: econometric analyses of routinely collected data - Andrew Street; Nils Gutacker; Chris Bojke; Nancy Devlin; Silvio Daidone (Health Services and Delivery Research, 2014)
Background: It is important that NHS resources are used to their full extent, but efforts to reduce costs may have an adverse effect on patient outcomes. Our research is designed to provide a better understanding of the inter-relationship between costs and health outcomes among NHS providers (hospitals) for common surgical procedures. Objectives: In England, patient-reported outcomes measures (PROMs) are collected from patients undergoing one of four elective procedures: unilateral hip replacement, unilateral knee replacement, groin hernia repair and varicose vein surgery. We identify variation in patient-reported outcomes (PROs) across hospitals, assess the relationship between the cost and outcomes among NHS hospitals for these procedures, and determine the extent to which variations in outcomes and costs are due to differences in hospital performance. Data sources: We link Hospital Episode Statistics (HES) data with reference cost data and PROM data for patients having the four treatments between April 2009 and March 2010. Methods: The first part of the empirical analysis focuses on variation in different dimensions of self-reported health status. We argue that each of the EuroQol-5D questionnaire (EQ-5D; European Quality of Life-5 Dimensions) dimensions should be assessed separately. Our graphical summary of the differential impact that hospitals have on PROs indicates the probability of reporting a given health outcome and shows how these probabilities vary across EQ–5D dimensions and hospitals. The second part of the empirical analysis focuses on the performance of hospitals and the inter-relationship between PROs and resource use. Results: We find that poorer post-treatment health status is associated with lower initial health status, higher weighted Charlson score, more diagnoses and lower socioeconomic status. We find significantly unexplained variation among hospitals in outcomes for patients undergoing hip replacement, knee replacement or varicose vein surgery, but not for hernia patients. For all four treatments we find significant unexplained variation in resource use among hospitals, whether measured by cost of treatment or length of stay. This suggests that hospitals can improve their utilisation of resources. Limitations: Our analyses are based on the HES. If data are missing from the medical record, or extracted and coded inaccurately, HES will contain errors. Hospitals should minimise these errors. Our study suffers from a large number of missing data, mainly because some hospitals were better than others at administering the baseline survey. Conclusions: There is no general evidence that hospitals with lower resource use have worse health outcomes. There is a significant positive correlation for varicose veins, but this is sensitive to the choice of resource use and PRO measures. For hip and knee replacement the correlation is either insignificant or negative (depending on the resource use and PRO measures), implying that promoting health outcomes and controlling costs are not contradictory objectives. Indeed, we are able to identify hospitals with better than expected outcomes where resource use is below average. Future research should address how to handle missing data, evaluate hospital performance within the broader health economy, communicate PROMs to prospective patients, evaluate the impact of PROMs on patient choice and provider behaviour and evaluate PROMs for people with chronic conditions. Funding: The National Institute for Health Research Health Service and Delivery Research programme.